Computational evidence for intramolecular hydrogen bonding and nonbonding X···O interactions in 2'-haloflavonols - Fonseca, Tânia A. O.; Freitas, Matheus P.; Cormanich, Rodrigo A.; Ramalho, Teodorico C.; Tormena, Cláudio F.; Rittner, Roberto (Beilstein Journal of Organic Chemistry, 2012)
The conformational isomerism and stereoelectronic interactions present in 2'-haloflavonols were computationally analyzed. On the basis of the quantum theory of atoms in molecules (QTAIM) and natural bond orbital (NBO) analysis, the conformer stabilities of 2'-haloflavonols were found to be dictated mainly by a C=O···H–O intramolecular hydrogen bond, but an unusual C–F···H–O hydrogen-bond and intramolecular C–X···O nonbonding interactions are also present in such compounds.
Keywords: conformational analysis; 2'-haloflavonols; intramolecular hydrogen bond; nonbonding interactions; theoretical calculations

(untitled) - Beijer, F. H.; Kooijman, H.; Spek, A. L.; Sijbesma, R. P.; Meijer, E. W. (Angew. Chem., Int. Ed., 1998)

(untitled) - Pinheiro, J. R.; Bitencourt, M.; da Cunha, E. F. F.; Ramalho, T. C.; Freitas, M. P. (Bioorg. Med. Chem., 2008)

(untitled) - Duarte, C. J.; Freitas, M. P. (J. Mol. Struct., 2009)

(untitled) - Dunitz, J. D.; Taylor, R. (Chem.–Eur. J., 1997)

(untitled) - Mallory, F. B.; Mallory, C. W.; Baker, M. B. (J. Am. Chem. Soc., 1990)

(untitled) - Matta, C. F.; Castillo, N.; Boyd, R. J. (J. Phys. Chem. A, 2005)

(untitled) - Palusiak, M.; Grabowski, S. (J. Struct. Chem., 2008)

(untitled) - Grabowski, S. J.; Małecka, M. (J. Phys. Chem. A, 2006)

(untitled) - Alkorta, I.; Elguero, J. (Struct. Chem., 2004)

(untitled) - Zordan, F.; Brammer, L.; Sherwood, P. (J. Am. Chem. Soc., 2005)

(untitled) - Metrangolo, P.; Resnati, G. (Science, 2008)

(untitled) - Verbeek, R.; Plomp, A. C.; van Tol, E. A. F.; van Noort, J. M. (Biochem. Pharmacol., 2004)

Atoms in Molecules: A Quantum Theory - Bader, R. F. W. (Oxford University Press, 1990)

(untitled) - Bader, R. F. W. (Chem. Rev., 1991)

(untitled) - Bader, R. F. W. (J. Phys. Chem. A, 1998)

(untitled) - Grabowski, S. J. (Chem. Rev., 2011)

(untitled) - Koch, U.; Popelier, P. L. A. (J. Phys. Chem., 1995)

(untitled) - Wallet, J. C.; Gaydou, E. M.; Molins, E.; Miravitlles, C. (Z. Kristallogr., 1994)

(untitled) - Lu, H.; Chang, D. J.; Baratte, B.; Meijer, L.; Schulze-Gahmen, U. (J. Med. Chem., 2005)

(untitled) - Wiseman, R. L.; Zhang, Y.; Lee, K. P. K.; Harding, H. P.; Haynes, C. M.; Price, J.; Sicheri, F.; Ron, D. (Mol. Cell, 2010)

(untitled) - Cioslowski, J.; Mixon, S. T. (J. Am. Chem. Soc., 1992)

(untitled) - Bickelhaupt, F. M.; Baerends, E. J. (Angew. Chem., 2003)

(untitled) - Bader, R. F. W. (Chem.–Eur. J., 2006)

(untitled) - Bader, R. F. W. (J. Phys. Chem. A, 2009)

(untitled) - Bader, R. F. W. (J. Phys. Chem. A, 2010)

(untitled) - Rozas, I.; Alkorta, I.; Elguero, J. (J. Am. Chem. Soc., 2000)

(untitled) - Espinosa, E.; Alkorta, I.; Elguero, J.; Molins, E. (J. Chem. Phys., 2002)

(untitled) - Bondi, A. (J. Phys. Chem., 1964)

The Nature of the Hydrogen Bond: Outline of a Comprehensive Hydrogen Bond Theory - Gilli, G.; Gilli, P. (Oxford University Press, 2009)

(untitled) - Rosenthal, J.; Schuster, D. I. (J. Chem. Educ., 2003)